Adhesio interthalamica and cavum septum pellucidum in mesial temporal lobe epilepsy. - Trzesniak, Clarissa; Linares, Ila; Coimbra, Érica; Júnior, Alexandre; Velasco, Tonicarlo; Santos, Antonio; Hallak, Jaime; Sakamoto, Americo; Busatto, Geraldo; Crippa, José; Linares, Ila M; Coimbra, Érica R; et al. (Brain Imaging & Behavior, 2016)
The absence of the adhesio interthalamica (AI; also called interthalamic adhesion or massa intermedia) and the presence of a large cavum septum pellucidum (CSP) later in life have been related to neurodevelopmental alterations and have not been systematically investigated in epilepsy to date. This study carried out a MRI evaluation of the AI and CSP in a large sample with mesial temporal lobe epilepsy (MTLE). A total of 179 patients, classified according to the side of the epileptogenic focus, and 156 age- and sex-balanced healthy controls were assessed. Between-group comparisons of the prevalence and length of both AI and CSP were conducted. Neuropsychological assessments were also performed in 160 MTLE patients. The patients exhibited reduction in the AI prevalence (P < 0.05; FDR-uncorrected) and length (P < 0.05; FDR-corrected) when compared to controls. Patients without AI showed lower scores in a proportion of neuropsychological tests than patients with AI. No CSP differences were found between MTLE patients and controls. These results support that AI anomalies have clinical significance in MTLE, as well as indicate that neurodevelopmental alterations may be implicated in this disorder.